2021
DOI: 10.7241/ourd.2021e.6
|View full text |Cite
|
Sign up to set email alerts
|

A Clinico-epidemiological study of patients with lichen planus and associated metabolic complications at a tertiary care centre

Abstract: Background: An association between lichen planus and systemic disorders such as diabetes mellitus, dyslipidemia and metabolic syndrome has been reported. Aim: To assess the clinico-epidemiological profile of lichen planus, evaluate prevalence of underlying metabolic complications and compare the clinical profile of patients with and without metabolic syndrome. Material and methods: All the patients with lichen planus attending dermatology out patient department of a tertiary care centre in South Rajasthan ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…Our study showed a significant association of Metabolic Syndrome in patients with LP as reported previously 12,13,15,22 . Among patients with Metabolic Syndrome, the majority were females which is in accordance with a study by Saxena et al 15 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study showed a significant association of Metabolic Syndrome in patients with LP as reported previously 12,13,15,22 . Among patients with Metabolic Syndrome, the majority were females which is in accordance with a study by Saxena et al 15 .…”
Section: Discussionsupporting
confidence: 93%
“…21 Our study showed a significant association of Metabolic Syndrome in patients with LP as reported previously. 12,13,15,22 Among patients with Metabolic Syndrome, the majority were females which is in accordance with a study by Saxena et al 15 The gender difference might be due to the predominant female population in our study. Metabolic Syndrome was predominant in the 4 th decade in our study however, Kurian et al, and Rana et al reported metabolic syndrome predominantly in the 5 th and 6 th decade respectively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, the youngest affected person was 5 years old, and the oldest was 76 years old, which is similar to the study conducted by Gupta et al 6 Our study's male to female ratio of 0.72:1 is comparable to that of Sharma et al (0.76:1) Parihar et al (0.8:1) which indicates a female preponderance. 4,7 Figure 4: Associations of different types of lichen planus.…”
Section: Discussionmentioning
confidence: 99%
“…3 Diabetes mellitus (DM), HTN, Hypothyroidism, and dyslipidemia are a few metabolic conditions that have been associated to the disease. 4 LP may serve as an external indicator of underlying immune and metabolic dysfunction. 5 Dermoscopy helps in differentiating from other mimicking dermatoses, often obviating the need for a skin biopsy.…”
mentioning
confidence: 99%